Using Hierarchical Multivariate Analysis to Examine Interactions Between Alternative Appraisals of Cancer and Virtual Health Support Among Middle-Aged and Older Internet Users: Predicting Positive Self-Reappraisal After Cancer. (November 2013) - Seçkin, Gül
The advent of online communication is transforming how older adults find social support with a community of peers who cope with similar health issues. This article explores whether participation in virtual health support groups demonstrates a significant interaction with users' appraisal of their illness experience and predicts self-reappraisal among adults 50 years of age and older ( N = 157). Hierarchical multiple regressions demonstrate the significance of the combined effect of virtual health support and its interaction with illness appraisal measures to predict the outcome variable of self-reappraisal. The results indicate that even though appraisal of cancer as a traumatic experience reduces positive self-reappraisal, those who appraised their illness to have been a traumatic experience perceived virtual support to be more influential on their sense of positive change after cancer. In contrast, perceived benefit of virtual support on positive self-appraisal is reduced if illness is appraised as an opportunity for personal growth.